Emergency Department Telemedicine Is Used for More Severely Injured Rural Trauma Patients, but Does Not Decrease Transfer: A Cohort Study. (February 2017) - Mohr, Nicholas M.; Harland, Karisa K.; Chrischilles, Elizabeth A.; Bell, Amanda; Shane, Dan M.; Ward, Marcia M.
Abstract: Objectives: Traumatic injury is a leading cause of death in the United States, and rural populations are at increased risk of injury and death. Rural residents have limited access to trauma care, and telemedicine has been proposed as one strategy to improve the provision of trauma care locally. The objective of this study was to describe patient‐level factors associated with telemedicine consultation in North Dakota critical‐access hospital (CAH) emergency departments (EDs) and to measure the association between telemedicine consultation and interhospital transfer. Methods: Observational cohort study of all adult (age ≥ 18 years) trauma patients treated in North Dakota CAH EDs with an active telemedicine subscription between 2008 and 2014. Trauma cases were identified from the North Dakota Trauma Registry, and telemedicine‐enabled care was determined using a probabilistic linking algorithm with the call records of the predominant telemedicine network in North Dakota. Multivariable generalized estimating equations were used to identify factors associated with telemedicine consultation and to measure the association between telemedicine consultation and interhospital transfer, adjusting for patient, injury, and hospital factors. Results: Of the 9, 281 North Dakota trauma patients seen in CAHs, 2, 837 were treated in an ED with an active telemedicine subscription. Telemedicine was consulted for 11% of all trauma patients in telemedicine‐capable EDs. Factors associated with telemedicine consultation included higher Injury Severity Score, penetrating injuries, burns, hypotension, tachycardia, and ambulance transport. Adjusting for severity of illness, injury mechanism, and type of injury, telemedicine use was not associated with interhospital transfer (adjusted odds ratio = 1.28, 95% confidence interval = 0.94 to 1.75). Conclusion: Emergency department–based telemedicine consultation is requested for the most severely injured rural trauma patients, especially with those with penetrating trauma, burns, and abnormal presenting vital signs. Telemedicine consultation was not independently associated with increased probability of transfer. Future work should evaluate how telemedicine impacts the timeliness of care and specific care interventions.